Sewage water irrigation: Importance and associated risk - Dotaniya, M. L.; Saha, J. K.; Meena, V. D. (Indian Farming, 2018)
Heavy metal toxicity is a global issue and spreading with a faster rate in non-contaminated areas. Developed countries had made various environmental policies to protect natural resources and provide a healthy environment for the better life. It is a time to act positively to save the natural resources, mostly water and land. Safe use of sewage water for agricultural purpose and the use of various phyto-remediation techniques to minimize the toxic metals concentration in soil and prevent leaching into water-bodies. Apart from these, regular monitoring of sewage and irrigated field in physio-chemical properties of soils.